(untitled) (Journal of the College of Basic Education, 2022)
Cloud point extraction (CPE) is a separation technique on the basis of phase separation properties of non-ionic surfactant above the cloud point temperature and the solubilizition phenomena of surfactant rich phase. Cloud point extraction exhibits many attractive advantage such as simplicity, low lost, high enrichment factor, non flammable, non volatile and less toxic surfactant, moderate extraction conditions and friendliness to the environment. A method passed on the cloud point extraction (CPE) for the trace analysis of Cu (II) in water samples is described in this study. The analyte in the initial aqueous solution are complexed with methionine at pH=8 and 5mL of 10% (v/v) Triton x-100 is added as surfactant. Following phase separation at (85 ) based on the cloud point of the mixture and dilution of the surfactant-rich phase with acidified methanolic solution. The enriched analyte are determined by Uv-visible spectrophotometry. After optimization of the complexation and extraction conditions, the preconcentration and enrichment factor of Cu (II) was found to be 90,89 respectively. Under optimum conditions like pH, methionine concentration, surfactant concentration, operation temperature and electrolyte effect, calibration graph showed linear trend in range of (0.05-4) g with molar absorptivity (19621.5) L.mol-1cm-1 Sandell’s sensitivity and detection limit of 0.0032 µg.cm-2,0.0071 µg/mL respectively for copper ion.